Implementasi Pasal 6 Ayat 2 Huruf B Peraturan Menteri Desa Nomor 13 Tahun 2020 Dalam Melestarikan Wisata Mangrove Di Desa Trans Patoa Kec. Helumo Kab. Bolaang Mongondow Selatan - pakaya, derireflan; Yunus, Yudin; Pede, Alber; Lamanasa, Syarif (Fakultas Hukum Universitas Ichsan Gorontalo, 2025)
ABSTRACT REFLAN PAKAYA. H1120052. THE IMPLEMENTATION OF ARTICLE 6 PARAGRAPH 2 LETTER B OF VILLAGE MINISTERIAL REGULATION NUMBER 13 OF 2020 IN PRESERVING MANGROVE TOURISM IN TRANS PATOA VILLAGE, HELUMO SUBDISTRICT, SOUTH BOLAANG MONGONDOW REGENCY This study aims to determine and analyze the implementation of the Village Ministerial Regulation Number 13 of 2020 in preserving mangrove tourism in Trans Patoa Village, Helumo Subdistrict, South Bolaang Mongondow Regency, and the factors that hinder the implementation of the Village Ministerial Regulation Number 13 of 2020 in preserving mangrove tourism in Trans Patoa Village, Helumo Subdistrict, South Bolaang Mongondow Regency. This study employs the Normative-Empirical Legal Research method, which involves legal case study analysis focusing on legal behavior products. The main focus is to observe how positive legal provisions and contracts are factually conducted in legal events that occur in society, with the aim of achieving predetermined targets. The results show that in the implementation of the Regulation of the Ministry of Village, Development of Disadvantaged Regions and Transmigration Number 13 of 2020, the foremost part is how the government, especially Trans Patao Village, can act as a provider of motivation for investors, communities, and business actors in the tourism sector. It is crucial to ensure that tourism growth can take place appropriately. Regulation Number 13 of 2020 Article 6 Paragraph 2 Letter B on the Use of Village Funds can be in the form of participation of ideas, namely in compiling each program to expedite the implementation of programs and activities related to mangrove forest conservation in Trans Patao Village, South Bolaang Mongondow and the budget issued by the Village government is felt to be still lacking for the development of Trans Patao Mangrove Tourism tourism. The recommendations are (1) Village governments are expected to increase the utilization of human resource potential to support village tourism management planning, (2) More importantly, they are expected to strengthen village tourism management efforts in order to provide sustainable benefits for the welfare of village communities in the future. Keywords: implementation, village ministerial regulation, mangrove conservation